The Characteristics of Significant Wave Height and Sea Surface Temperature In The Sunda Strait - Hanah Khoirunnisa; Muhammad Zainuddin Lubis; Wenang Anurogo (Journal of Applied Geospatial Information, 2017)
Sunda Strait has an important role in the water mass exchange from the Pacific Ocean and the Indian Ocean so that the oceanographic condition is strongly affected by seasonal factors. The purpose of this study is to observe the relationship and the characteristics of significant wave height (SWH) and sea surface temperature (SST) in the Sunda strait and its relationship with IOD. The method employed is spatial analysis, low-pass filter, and spectrum analysis by S-Transform, beside that the correlation between SST and SWH is analyzed by wavelet coherency. The period of SWH and SST is dominantly semiannual, at the time of winter monsoon (the Northeast Monsoon), the SWH was reaching up to 2,11 m, while at the summer monsoon, the SWH was reaching up to 3.62 m. Reversely, the SST increased during the winter monsoon. At the time of 2016 had been detecting by the negative IOD with the IOD index of -0.65 and it caused the SWH increased by 0.3 m than its average. Based on the wavelet coherence, the SWH and the SST have the coherence in the period of 8 to 16 days, especially in March to April, and June to August.